Selective Adsorption Properties of a Model Nano-Patterned Surface - Paweł Szabelski; Agnieszka Guz (Adsorption Science & Technology)
In this contribution, we have studied the influence of a periodic distribution of active sites on a model heterogeneous surface on the ability of that surface to preferentially adsorb molecules with a pre-defined shape. For this purpose, we used a simple analytical model in which a mixture of linear and bent rigid molecules composed of three identical segments was adsorbed onto a square lattice with different patterns of active sites. For each pattern and each type of molecule, the corresponding adsorption energy distributions (AEDs) were determined and used further for the calculation of the associated selectivities. It was demonstrated, that depending on the pattern formed by the active sites, the selectivity towards the bent molecule can vary quite considerably and that a suitable choice of surface pattern can maximize the selectivity. Apart from the adsorptive separation, we also considered the thermal desorption of the mixture and model one-component and binary desorption spectra from the nano-patterned surfaces. The results of the temperature-programmed desorption modelling were compared with those obtained for equilibrium adsorption. It was shown that the pattern which provides the highest selectivity in equilibrium adsorption does not have to be optimal when used in the separation of molecules by temperature-programmed desorption.